2021
DOI: 10.3389/fcell.2021.673838
|View full text |Cite
|
Sign up to set email alerts
|

Construction of a Promising Tumor-Infiltrating CD8+ T Cells Gene Signature to Improve Prediction of the Prognosis and Immune Response of Uveal Melanoma

Abstract: BackgroundCD8+ T cells work as a key effector of adaptive immunity and are closely associated with immune response for killing tumor cells. It is crucial to understand the role of tumor-infiltrating CD8+ T cells in uveal melanoma (UM) to predict the prognosis and response to immunotherapy.Materials and MethodsSingle-cell transcriptomes of UM with immune-related genes were combined to screen the CD8+ T-cell-associated immune-related genes (CDIRGs) for subsequent analysis. Next, a prognostic gene signature refer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 58 publications
1
14
0
Order By: Relevance
“…Given that TIME’s immune profile, including CD8 + T-cell-related genes, has been shown to correlate with prognosis ( 36 , 37 ), and based on PTPRO’s regulatory role in promoting CD8 + T-cell infiltration, we further investigated the association between CD8 + T-cell-related genes and PTPRO. By analyzing the scRNA-seq data from the GSE110686 cohort, 127 CD8 + T-cell marker genes were confirmed ( Figure 3A , Supplementary Figure S2A ).…”
Section: Resultsmentioning
confidence: 99%
“…Given that TIME’s immune profile, including CD8 + T-cell-related genes, has been shown to correlate with prognosis ( 36 , 37 ), and based on PTPRO’s regulatory role in promoting CD8 + T-cell infiltration, we further investigated the association between CD8 + T-cell-related genes and PTPRO. By analyzing the scRNA-seq data from the GSE110686 cohort, 127 CD8 + T-cell marker genes were confirmed ( Figure 3A , Supplementary Figure S2A ).…”
Section: Resultsmentioning
confidence: 99%
“…Other evidence reinforced the relationship between immune cell infiltration and prognosis, with the exception of some genetically distinct subgroups [ 28 ]. Recently, a bioinformatic analysis and CD8+ gene signature confirmed the prognostic role of CD8 in UM [ 17 , 18 ]. In addition, a recent study performing single cell analyses of the tumor and the microenvironment in primary and metastatic UMs outlined genomic complexity, as well as revealing a different subset of CD8+ T cells expressing checkpoint marker LAG3 but not PD1 or CTLA4 [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the context of UM, inflammatory cell infiltration has been described within and at the periphery of the tumor, especially when epithelioid cells are predominant [ 7 ]. High densities of tumor-associated macrophages (TAMs) and tumor-infiltrating lymphocytes (TILs) in primary UM have been correlated with a higher metastasis risk and worse prognosis [ 16 , 17 , 18 ]. Previous studies have shown that most TAMs in UMs are M2-type cells expressing CD68+ and CD163+, and survival was significantly reduced among patients with a high M2 macrophage and T cell density [ 19 , 20 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Biomarker-based patient stratification has gained much attention, which calls for more accurate evaluation of these molecular properties. Especially for those patients who receive immunotherapy, the comprehensive analysis of the risk score, as well as immune checkpoint expression, could hopefully foretell the reactivity of these patients and therefore screen out the appropriate patients for immunotherapy [32][33][34]. Immune checkpoints expressed on cancer cells or cancer-associated immune cells have drawn substantial attention as promising treatment targets nowadays [35].…”
Section: Discussionmentioning
confidence: 99%